EFFECTIVE KNOWLEDGE TESTS AND FEEDBACK IN FUNCTION OF IMPROVING THE STUDENTS' STUDY - Duško Bjelica; Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
One of the most important issues in the project "National frame of qualifications and quality providing in education", run by the EU Delegation in Montenegro, is improvement of students' study through effective knowledge tests and feedbacks. Knowledge tests do not only represent a problem of knowledge evaluation, but they significantly determine instructional design of the teaching process. Process of organisation and structuring of an exam, besides feasibility and applicability aspects, also has educative aspects. The knowledge tests should motivate a student to improve their own education as well as to motivate them to further studying. An exam should not be considered as individual method of knowledge evaluation, but as a procedure that will be pervaded with the educative programme. In that sense, availability of good-quality feedback enables the students to self-correct, and the chosen methods of examination have to provide relevant results